The legal status of news agencies and the impact of politics on their work : “An analytical Study” - Anwar Saleh, Ammar; Dino, Banstan (Humanities Journal of University of Zakho, 2023)
The goal of news agencies is to get information from their original sources in order to facilitate the flow of news, as news agencies are considered the main source of news around the world, and their work is evident in collecting news around the clock through a wide network of journalists and media professionals to collect news and send it to the agency’s sub-center or main In order to process and edit news and information, and it is sent to the audio-visual media in addition to newspapers, magazines and newspapers, and through this research we will address the legal status of news agencies by defining news agencies and what these agencies enjoy of rights and obligations they bear by defining international rules And the internal organization of the rights and obligations of agencies. We will also discuss the political status of news agencies and the impact of politics on news agencies. It has become clear to us that it is not easy to find an adequate and comprehensive definition of news agencies and to get acquainted with the legal system that applies to news agencies, because agencies take different forms upon incorporation, in addition to that these agencies usually establish more than one main center in order to be able to collect news and pictures easily and cover more A possible space to carry out its work, so its main centers are usually distributed around the world, and this leads as a result to not knowing the legal system that applies to foreign news agencies, similar to multinational news agencies, and through research we reached a set of recommendations, including we recommend the Iraqi legislator to enact a special law In it, it deals with the issue of the work of foreign news agencies, and the law deals with how to open branches of foreign agencies and determine the rights and obligations of these agencies, in addition to dealing with the employment of Iraqi journalists and their work contracts in these agencies, as there is no law that deals with these issues.